Aplicación de técnicas electroanalísticas en la determinación de cadmio en agua potable. - Ortiz Mejia, Diana Aracely (2015)
In recent years they have developed analytical techniques for the determination of heavy metals such as cadmium, which confer the possibility of reducing both energy consumption of reagents.